2014
DOI: 10.1634/theoncologist.2014-0057
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer, BRCA Mutations, and Attitudes Regarding Pregnancy and Preimplantation Genetic Diagnosis

Abstract: Background. Women with premenopausal breast cancer may face treatment-related infertility and have a higher likelihood of a BRCA mutation, which may affect their attitudes toward future childbearing. Methods. Premenopausal women were invited to participate in a questionnaire study administered before and after BRCA genetic testing. We used the Impact of Event Scale (IES) to evaluate the pre-and post-testing impact of cancer or carrying a BRCA mutation on attitudes toward future childbearing. The likelihood of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
0
11
2
1
Order By: Relevance
“…To begin, our findings reinforce previous research articulating a tension between cancer risk management (i.e., preventative surgeries) and life goals (i.e., having children, Donnelly et al 2013;Rubin et al 2014;Werner-Lin 2008), yet reveals previvors' willingness to push their preventative surgeries back in order to have (more) children. This is in contrast to previous research that has found that women who test positive for a BRCA mutation were less likely to want more children after learning their genetic test results (Smith et al 2004;Woodson et al 2014). This finding also relates to other reproductive decision-making in other genetic contexts.…”
Section: Discussioncontrasting
confidence: 89%
“…To begin, our findings reinforce previous research articulating a tension between cancer risk management (i.e., preventative surgeries) and life goals (i.e., having children, Donnelly et al 2013;Rubin et al 2014;Werner-Lin 2008), yet reveals previvors' willingness to push their preventative surgeries back in order to have (more) children. This is in contrast to previous research that has found that women who test positive for a BRCA mutation were less likely to want more children after learning their genetic test results (Smith et al 2004;Woodson et al 2014). This finding also relates to other reproductive decision-making in other genetic contexts.…”
Section: Discussioncontrasting
confidence: 89%
“…In a case-control study comparing fertility desires of 25 BRCA1 carriers vs. 62 non-carriers, Smith et al reported that female carriers were significantly less likely to report a desire for future children (Smith et al, 2004). A survey study found that following disclosure of a BRCA mutation, women (especially those >36 years of age) were less interested in future childbearing (Woodson et al, 2014). In contrast, very few of the women in our study whose families were not complete at the time of survey decided against having children in light of their carrier status.…”
Section: Discussionmentioning
confidence: 99%
“…Before the start of any systemic therapy, all AYAs with breast cancer should be offered referral to a reproductive endocrinologist for either embryo or oocyte cryopreservation. Preimplantation genetic diagnosis, selecting unaffected embryos for implantation, is an option for carriers of BRCA mutations or other cancer predisposition syndromes . Ovarian suppression with goserelin during chemotherapy is an option for AYAs with hormone‐receptor‐negative breast cancer, decreasing the incidence long‐term ovarian failure and possibly improving pregnancy outcomes …”
Section: Special Issues For Ayas With Breast Cancermentioning
confidence: 99%